Using narrative inquiry for educational research in the Asia Pacific - Trahar, Sheila; Yu, Wai Ming (Routledge research in education, 2015)
"Narrative inquiry is used more widely in the UK, the USA, Canada, Australia, New Zealand and the Northern European countries. It is gaining in popularity in Hong Kong, Macao and Mainland China, but dominated by quantitative and more traditional qualitative approaches in these contexts, narrative inquirers can find it problematic to have the value of their work acknowledged. This book demonstrates creatively, accessibly and rigorously the ways in which narrative inquiry as a methodological approach, already more firmly established in Australia and New Zealand, is gaining a foothold in other parts of the Asia Pacific region. A related aim of the book is to identify the affordances of this approach that render it particularly suitable for a range of research topics. Comparisons will be made between the use of narrative inquiry in the Confucian heritage cultures (CHC) of Hong Kong, Mainland China, Singapore, Macao and the Anglo-Celtic cultures of Australia and New Zealand"--Provided by publisher.